A model of complex equity funding for contingent acquisitions – a case study of non-interest bearing convertible unsecured loan stock - Hillier, David; Marshall, Andrew P. (Journal of Corporate Finance, 1998)
Equity finance, raised through a rights issue, is a popular method for funding acquisitions in UK. Acquisitions are often contingent on a number of external factors. This paper uses a binomial asset pricing model to examine the effects on the share price of a company that undertakes an equity rights issue to fund a contingent acquisition. We consider a new equity rights issue instrument called a non-interest bearing convertible unsecured loan stock (NICULS), specifically designed to deal with contingent acquisitions. We develop our model in two stages. First, we assume perfect foresight on behalf of the issuing company and investors and, secondly, we develop a model that relaxes these restrictive assumptions, called a NICULS model. Our preliminary findings based on a case study show that there is a dip in the share price over and above that expected by the dilution effect of the increased number of shares. We interpret this either as a natural consequence of the market's evaluation of the value of the investments for which the funds were raised or as a signal imparted by the company about the future investment opportunities of the company. We have also found that the market's expectation of the success of the acquisition attempt has a direct and significant effect on the observed dip in the share price.